PEMILIHAN TEMPAT BERSALIN PADA IBU HAMIL TRIMESTER III SELAMA PANDEMIC COVID-19 DI KOTA PEKANBARU - Lidia Fitri; Evis Ritawani Hsb; Tety Mega Pransiska N (Ensiklopedia of Journal, 2022)
Pregnancy is a natural and physiological process. Most of the pregnant women have determined the place where to give birth. The Indonesian Health Profile in 2019 noted that there were 90,95% of pregnant women choosing health facilities. But due to the increasing cases of the covid-19 pandemic during 2021 causing mother who will be worried to choose the place of birth. The initial survey showed 3 pregnant women have not decided and choose a place to give birth because they are worried about giving birth during the Covid-19 period. The purpose of this study was to determine the description of the selection of the place of birth for pregnant women in the third trimester during the COVID-19 period in Pekanbaru City. This type of quantitative analytical research with descriptive design. The population of all trimester III pregnant women in Pekanbaru City. A sample of 30 taken using the Accidental sampling method. Based on the results of the study, it was found that 21 people (70%) of pregnant women in the third trimester choose the place of birth in a health facility on the grounds that since the beginning of pregnancy they had carried out a pregnancy examination at that place, namely in the midwife clinic with the highest birth attendant midwife. It is advisable for pregnant women in the third trimester to maintain the choice of place of delivery in health facilities. Keywords : Choice of place of birth, Pregnancy, COVID-19Kehamilan adalah suatu proses alamiah dan fisiologis. Sebagian besar ibu hamil sudah menentukan tempat dimana akan melakukan persalinan. Profil Kesehatan Indonesia tahun 2019 mencatat bahwa terdapat 90,95% ibu hamil memilih di fasilitas kesehatan. Tetapi karena meningkatnya kasus pandemi COVID-19 selama tahun 2021 menyebabkan ibu yang akan bersalin menjadi khawatir untuk memilih tempat bersalin. Survei awal menunjukan 3 orang ibu hamil belum menentukan dan memilih tempat bersalin karena merasa khawatir saat akan bersalin selama masa COVID-19. Tujuan penelitian untuk mengetahui gambaran pemilihan tempat bersalin pada ibu hamil trimester III selama masa COVID-19 di kota Pekanbaru. Jenis penelitian kuantitatif dengan desain deskriptif. Populasi seluruh ibu hamil trimester III di Kota Pekanbaru. Sampel berjumlah 30 yang diambil dengan teknik purposive sampling. Hasil penelitian menunjukkan bahwa sebanyak 21 orang (70%) ibu hamil trimester III memilih tempat bersalin di fasilitas kesehatan dengan alasan sejak awal kehamilan sudah melakukan pemeriksaan kehamilan di tempat tersebut. Disarankan pada  ibu hamil trimester III untuk tetap mempertahankan pemilihan tempat bersalin di fasilitas kesehatan. Kata Kunci    : Pemilihan Tempat Bersalin, Ibu Hamil, Covid-19